Exploring the Fundamentals of Python Programming: A Comprehensive Guide for Beginners - Burak Elhalid, Osama; Alhelal, Zaynelabdin; Hassan, Samer (Elsevier BV, 2023)
This scientific article entitled 'Exploring the Fundamentals of Python Programming: A Comprehensive Guide for Beginners' provides a comprehensive overview of the basics in Python programming, and is intended for beginners in the field of programming. The article discusses the history and importance of Python, then goes on to explain how to install Python and start writing programs with it using a text editor. It delves into the basics such as variables, data types, control flow, and functions. The article provides practical examples to illustrate how Python can be used to solve simple problems. In addition, the article deals with useful references and resources for readers to further delve into programming in Python.
Keywords: Python Basics; Beginner Programming; Programming Education; [INFO] Computer Science [cs]; Beginner Programming Python Basics Programming Education